The Effectiveness of Karisma Instructional Model in Fostering The Characters and Increasing Students’ Learning Outcomes of 4th Gradeelementary School Students (Journal of Primary Education, 2018)
Educational problems require an innovative learning system and research to solve the problems. Research with learning model is line of way to improve the quality of education. The objectives of the research are to describe the way of implementing Karisma learning model, to know the difference of character improvement and learning outcomes, and to know the problems that occurred when implementing the Karisma learning model in Elementary School. Type of research which was used in the research was experiment, while the data analysis technique which was used was two way variant (two way anava) The result of research of the significance of students’ character improvement for factor of student attitude learning model is 0,026 <0,05, or Ftable = 3,027 and Fcount = 3,683. Students’ learning outcomes generally improved with the average of SD LB score 88, SD MR score 74. SD SM scores 82, and SD DD score 78. The results of study by using Karisma learning modelare better, that is 83.29, compared with conventional model which is only scored 74.76. Response data shows that students feel active and do discussion with score of 83.2%. Based on the data analys, schools that implement the Karisma learning model have more positive impact when it is implemented.